Changes in the Arctic environment and the law of the sea - Nordquist, Myron H.; Heidar, Tomas H.; Moore, John Norton, 1937- (Center for Oceans Law and Policy (Series), 2010)
While the Arctic Ocean has long been covered with ice, recent changes in climate have caused the ice to melt, spurring conservation challenges to both the region's environment and biodiversity, as well as new opportunities for navigation and natural resource development. Changes in the Arctic Environment and the Law of the Sea offers policy and legal guidance in response to these new challenges. Synthesizing the presentations of leading experts at the meeting ""Changes in the Arctic Environment and the Law of the Sea"" held in May, 2009 in Seward, Alaska, the topics explored in this volume incl.